Addressing Common Questions Encountered in the Diagnosis and Management of Cardiac Amyloidosis. Issue 14 (4th April 2017) - Maurer, Mathew S.; Elliott, Perry; Comenzo, Raymond; Semigran, Marc; Rapezzi, Claudio
Abstract : Advances in cardiac imaging have resulted in greater recognition of cardiac amyloidosis in everyday clinical practice, but the diagnosis continues to be made in patients with late-stage disease, suggesting that more needs to be done to improve awareness of its clinical manifestations and the potential of therapeutic intervention to improve prognosis. Light chain cardiac amyloidosis, in particular, if recognized early and treated with targeted plasma cell therapy, can be managed very effectively. For patients with transthyretin amyloidosis, there are numerous therapies that are currently in late-phase clinical trials. In this review, we address common questions encountered in clinical practice regarding etiology, clinical presentation, diagnosis, and management of cardiac amyloidosis, focusing on recent important developments in cardiac imaging and biochemical diagnosis. The aim is to show how a systematic approach to the evaluation of suspected cardiac amyloidosis can impact the prognosis of patients in the modern era. Abstract : Supplemental Digital Content is available in the text.